Geographic Information System of Oil Palm Location Based on Android - Olha Musa; Zainudin Sidik (The IJICS (International Journal of Informatics and Computer Science), 2021)
This study designs a geographic information system (GIS) that always adapts to the current development of information technology, many researches are carried out to encourage the emergence of new discoveries in the world of technology. One of the uses of GIS is to make it easier for decision makers to determine the policies to be taken, especially those related to spatial aspects. So far, the data and information on the location of plantation lands that are presented are still in the form of reports containing numbers and text, while maps are still presented manually on books or paper, so a geographic information system is needed that can provide information to companies about the location of oil palm lands. easy and fast. The purpose of this study is to build an android-based geographic information system for oil palm land in Mootilango District. The method used is the Research and Development method, this application is designed using PHP and HTML programming language software, namely Macromedia Dreamwever, Java programming language using Android studio, and tools for modeling using UML (Unified Modeling Language). By testing the system using whitebox and blackbox testing, with this test the correct graph flow is obtained as a sample of researchers in testing. The results of this research are the implementation of the system that is designed to be suitable for use and can have a good impact on the company, so that this system can make it easier for companies to get palm oil information quickly anytime and anywhere. Based on the blackbox test table, the results are appropriate